Association of malocclusion with temporomandibular disorders:a cross-sectional study - Ângelo, David Faustino (2024)
Background/Objectives: Temporomandibular disorders (TMD) encompass a range of musculoskeletal and neuromuscular conditions affecting the temporomandibular joint (TMJ) and associated structures. This cross-sectional study, conducted in a Portuguese TMD department, aimed to assess the relationship between malocclusion and TMD severity. Methods: Data on demographic variables, TMD clinical symptoms, and malocclusion classes were collected using the EUROTMJ database. The Chi-square test (χ2) identified associations, with their intensity measured by Cramér’s V (φc). Results: The study included 1170 patients (932 females and 238 males), with a mean age of 41.73 ± 16.80 years. Most patients exhibited Angle Class I malocclusion (85.5%), followed by Angle Class II (13.5%) and Angle Class III (1.1%). Class II malocclusion was associated with increased TMD severity (p < 0.001), higher myalgia levels (p = 0.002), more frequent disc displacement without reduction (p = 0.002) and lower maximum mouth opening values (Class II: 38.13 ± 7.78 mm, Class I: 39.93 ± 8.67 mm). Significant associations were also found between malocclusion type and arthralgia (p = 0.021), mouth-opening limitation (p = 0.016), and TMJ crepitus (p = 0.017). In cases of malocclusion, the presence of oral signs of bruxism explained the degree of myalgia, disc displacement, and severity (p = 0.003; p = 0.048; p = 0.045). Conclusions: This study highlights that (1) the most common type of dental malocclusion in TMD patients was Class I; (2) Class II malocclusion was associated with increased TMD severity and oral signs of bruxism; and (3) Class III was rarely observed in TMD consultation. The findings suggest that bruxism behavior in cases of malocclusion may be significant in TMD.